Outpatient antidepressant drug use in children and adolescents in Germany between 2004 and 2011. Issue 2 (20th November 2016) - Schröder, Carsten; Dörks, Michael; Kollhorst, Bianca; Blenk, Tilo; Dittmann, Ralf W.; Garbe, Edeltraut; Riedel, Oliver
Abstract: Purpose: Recent studies on the utilization of antidepressant drugs in minors are scarce, methodologically limited, and do not factor in off‐label use sufficiently. Beyond that, little is known about the short treatment durations that have been observed for many young antidepressant users. The present study examined antidepressant use in pediatric patients aged 0 to 17 years over time, investigated changes regarding the prescribed drugs, analyzed underlying diagnoses, and assessed the rate of off‐label use. Methods: We used claims data of roughly two million individuals to calculate annual prevalence and incidence rates of antidepressant prescriptions for the years 2004 to 2011. Analyses were stratified by age, sex, and drug type. For antidepressant users, numbers of prescriptions, frequencies of disorders/diseases, and specialties of the prescribing physicians were examined. The share of off‐label prescriptions was calculated for each year. Results: The prescription prevalence of antidepressants ranged between 1.7 and 2.1 per 1000 minors. The use of tricyclic antidepressants decreased from 0.9 to 0.6 prescriptions per 1000 minors, while the use of selective serotonin reuptake inhibitors increased from 0.5 to 1.1. Of the patients with an antidepressant prescription, 46.4% only received one prescription. Depression was by far the most frequent diagnosis among all antidepressant users as well as among subjects with only one prescription. In 2011, 36.3% of all prescriptions were off‐label. Conclusions: The high proportion of single prescriptions, even in patients with a diagnosed depression, and the high rate of off‐label use are particularly noteworthy and should be further investigated in future studies. Copyright © 2016 John Wiley & Sons, Ltd.